Marketing Strategy Analysis on Features Live Shopping with Game Theory (Case Study: Live Shopping Users in Surabaya City) - Afiana, Nesya Fitri; Aryanny, Enny (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
In business competition, it is necessary to have a strategy in dealing with competition as a tool to improve business quality so that an appropriate and optimal strategy is needed for companies to win market share. This research aims to determine the optimum marketing strategy for the live shopping marketplace features of Shopee, Tokopedia, and Lazada to increase sales through the live shopping feature. One way that can be used to analyze the right marketing strategy is by applying game theory to find out the optimal strategy for players. The results of this study in Shopee’s first game against Tokopedia resulted in a game value of 26 so that Shopee, could increase profits from 23 to 26. At the same time, Tokopedia could reduce losses from 30 to 26. In the second game, Shopee against Lazada resulted in a game value of 21, so Shopee can increase profits from 15 to 21, while Tokopedia can reduce losses from 28 to 21. In the third game, Tokopedia against Lazada resulted in a game value of 19, so Tokopedia can increase profits from 15 to 19, while Lazada can reduce losses from 29 to 19.